1991
DOI: 10.1016/s0010-9452(13)80125-6
|View full text |Cite
|
Sign up to set email alerts
|

Apperceptive and Associative Forms of Prosopagnosia

Abstract: Three prosopagnosic patients were given four face tests, two perceptual (an unknown face identification test and an age estimation test) and two also implying memory (a familiarity check test and a famous face recognition test). The patients' performance was assessed with reference to the score distribution of the normal population. A patient was found to fail both perceptual and mnestic tests, without any noticeable difference between them. Also the second patient had poor scores on both kinds of tests, but h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
135
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(142 citation statements)
references
References 9 publications
5
135
0
2
Order By: Relevance
“…Indeed, there is some evidence that developmental prosopagnosia is often underpinned by various deficits in the domain of perception (e.g. De Renzi, Faglioni, Grossi & Nichelli, 1991) and a similar investigation in our laboratory suggests that this is also true for SRs (Bobak, Bennetts, Jansari, Parris & Bate, in preparation). Future work could consider individual differences in general visual processing and performance on applied tasks of face matching and face recognition.…”
Section: Discussionmentioning
confidence: 57%
“…Indeed, there is some evidence that developmental prosopagnosia is often underpinned by various deficits in the domain of perception (e.g. De Renzi, Faglioni, Grossi & Nichelli, 1991) and a similar investigation in our laboratory suggests that this is also true for SRs (Bobak, Bennetts, Jansari, Parris & Bate, in preparation). Future work could consider individual differences in general visual processing and performance on applied tasks of face matching and face recognition.…”
Section: Discussionmentioning
confidence: 57%
“…In the present patient both the baseline evaluation and the follow-up assessment revealed a composite clinical picture in which minor defects of configurational face analysis were associated with an impairment to experience visual familiarity for well-known faces, and a substantial impairment to associate visually perceived faces to preserved semantic information about people. This is no room here to tackle the controversial distinction between associative and apperceptive forms of prosopagnosia (De Renzi et al, 1991;Duchaine and Weidenfeld, 2003;s e eGainotti and Marra, 2011, for a recent review), but our data support the hypothesis that ILF is the most critical fibre pathway connecting regions of the core system of face processing (see Haxby et al, 2000;Catani and Thiebaut de Schotten, 2008), as proposed in the past (Benson et al, 1974;Habib, 1986;Kawahata and Nagata, 1989;Meadows, 1974;Takahashi et al, 1995). A damage of rILF would disconnect the occipital face area and the FFA from each other or from regions in the anterior temporal lobe and the precuneus (Catani et al, 2003), thus hampering modulation of right occipital lobe on temporal lobe activity.…”
Section: Discussionmentioning
confidence: 99%
“…2 In 22 of these cases, unfamiliar face recognition was tested only with the BFRT and/or the RMF [4,5,9,12,16,[17][18][19][20]23,28,30,35,36,47,48]. Because we have demonstrated that normal scores on these tests do not require intact unfamiliar face recognition, these cases should no longer be considered support for the dissociation.…”
Section: Implications For Theories Of Normal Face Recognitionmentioning
confidence: 99%